Pendekatan Pembelajaran Sains Berbasis Al-Qur'an di SDN Pekayon 03 Pagi - Gestika Rahmah; Heni Ani Nuraeni; Fauziah, Nur (Mu'allim, 2025)
Elementary education is a crucial stage in shaping students' character and understanding. This study aims to analyze the effectiveness of the Al-Qur'an-based science learning approach at SDN Pekayon 03 in integrating religious values with scientific concepts. This approach integrates relevant Quranic verses into science learning materials to enhance students' understanding of the relationship between science and spiritual values. The research employs a descriptive qualitative method, using observation, interviews, and documentation as data collection techniques. The findings reveal that this approach enhances students' motivation to learn, broadens their understanding of science concepts, and fosters awareness of the connection between knowledge and the greatness of God. Students become more active, show greater interest in the material, and develop a high sense of curiosity. However, the implementation faces challenges, such as time constraints and the need for integrated teaching resources.